Cardiology ward rounds - Ahmed, Shafique (Paramount Publishing Enterprise, 2013)
Cardiology ward rounds is an openn source of Cardiology for young minds to explore, learn and acquire knowledge in order to meet the needs of postgraduate examination. This comprehensive anthology of Cardiovascular medicines simplifies diagnosis and management in the form of bullet or numbered lists, tables and acronyms to make it easy-to-remember.